Issues raised during the Army after next spring wargame - Perry, Walt L. (RAND, 1999)
The Army After Next (AAN) wargames provide a structured forum for a discussion of national security issues associated with the nature of warfare in the early-to-mid 21st century. This report summarizes issues generated during the AAN Spring Wargame 1998. The wargame was set in 2021. The major game activity involved an attack by Red on the states on the south shore of the Persian Gulf. The United States was also involved in a multinational peacekeeping operation in Indonesia. In addition, continuing border conflict between India and Pakistan escalated dangerously during the game, eventually resulting in nuclear weapon use. These three separate events were designed to examine the role of AAN forces in global conflicts. Five dominant themes cut across the twelve issues identified in this study: rapid deployment into theater, asymmetric responses, urban warfare, homeland defense, and information operations.